Design, Optimization, and In vitro Evaluation of Gentamicin Sulfate-loaded Solid Lipid Nanoparticles for Ocular Administration - Venu, M.; Goudanavar, Prakash S. (Micro and Nanosystems, 2025)
BackgroundThe current study set out to formulate, Design, and assess Solid Lipid Nanoparticles (SLNs) loaded with Gentamicin sulfate.MethodsGlyceryl monostearate (GMS) was used as the lipid matrix in the formulation of solid lipid nanoparticles (SLNs) loaded Gentamicin sulfate through solvent evaporation and ultrasonication. To maximize the SLNs, a 32-level full factorial design was applied. The two independent variables selected were lipid concentration and sonication time. The dependent variables were PDI and particle size. The two dependent variables were particle size and % entrapment efficiency. The optimized formulation was subjected to various evaluation parameters like particle size, % entrapment efficiency, PDI, zeta potential, TEM analysis, pH, drug content, in vitro drug release, release kinetics, ex-vivo drug permeation, sterility test, isotonicity test, in vitro ocular irritation study and ex vivo corneal histopathology studies.ResultsThe optimized formulation showed a particle size of 178.2 nm, entrapment efficiency of 93.095%, and PDI of 0.246, where all these results were within ± 5% limits of predicted results suggested by software and statistically significant at 95% of the confidence interval. The optimized formulation showed sustained drug release with a maximum of 82.11 ± 0.34 till 8 hrs following the Higuchi drug release kinetics mechanism. The sterility test and isotonicity test confirmed that the formulation was sterile and isotonic with human blood. HET-CAM test proved that the optimized formulation exhibited neither irritability nor toxicity for ocular administration. A histopathology study confirmed that the formulation didn’t affect the structure of the cornea and hence the formulation was found to be safe for ocular administration.ConclusionBased on the obtained results, the study concluded that Gentamicin sulfate-loaded SLNs could be a promising novel formulation approach to address the limitations of commercial eye drops for treating ophthalmic bacterial conjunctivitis.
Keywords: zeta potential